Strengthening concrete using phosphate cement-based fiber-reinforced inorganic composites for improved fire resistance. (10th July 2019) - Ding, Zhu; Xu, Mu-Rui; Dai, Jian-Guo; Dong, Bing-Qin; Zhang, Ming-Jie; Hong, Shu-Xian; Xing, Feng
Graphical abstract: Highlights: The phosphate cement was used to produce fiber-reinforced inorganic polymer (FRiP) composites. The FRiP composites achieved excellent bonding performance with concrete substrate. The FRiP composites exhibited significantly improved fire resistance compared to FRP composites. Abstract: Fiber reinforced polymer (FRP) composites have been widely used for strengthening of concrete structures for many years. A critical concern for the FRP strengthening technology is the fire resistance. In this study, phosphate cement-based fiber-reinforced inorganic polymer (FRiP) composites were used to replace conventional fiber-reinforced polymer (FRP) composites to strengthen concrete beams for improved fire resistance. The performances of FRiP composites, FRiP-to-concrete interfaces and FRiP-strengthened concrete beams were examined both before and after fire exposure. It was demonstrated that the phosphate cement-based FRiP composites can significantly enhance the mechanical strength of the concrete beams. In addition, they exhibit much improved fire resistance as compared to the epoxy-based FRP composites.